Acetylene-based two-step diastereoselective synthesis of bridgehead dihydro-oxadiazines using ketones and hydrazine as the only reactants. Issue 18 (11th February 2019) - Schmidt, Elena Yu.; Semenova, Nadezhda V.; Ivanova, Elena V.; Tatarinova, Inna V.; Ushakov, Igor' A.; Vashchenko, Alexander V.; Trofimov, Boris A.
Abstract : Bridgehead dihydro-1, 3, 4-oxadiazines are synthesized by the acid-catalyzed diastereoselective reaction of hydrazine with 6, 8-dioxabicyclo[3.2.1]octanes, the products of the superbase-promoted self-organization of acetylene with ketones. Abstract : Pharmaceutically related bridgehead dihydro-1, 3, 4-oxadiazines are synthesized in up to 94% yield by the acid-catalyzed diastereoselective reaction of hydrazine hydrate with 6, 8-dioxabicyclo[3.2.1]octanes (6, 8-DOBCOs), the products of the superbase-promoted self-organization of acetylene with ketones. The synthesis covers a diverse range of alkylaromatic ketones having F-, Cl-, Br-, alkoxy-, CF3 - and aryl substituents in different positions of the aromatic rings.